Assessment of Groundwater Abstraction for Factories in Klang, Selangor - May, Raksmey; Muhamad Fuad, Bin Shukor; Kong, Sitha (2019)
Selangor is one of the most developed states in Malaysia based on industrial activities. Constant water supply to factories is a challenge for both authority and company manager. The reliable water source of groundwater is an option for companies in addition to the municipal water supply. To exploit the groundwater resources, Lembaga Urus Air Selangor (LUAS) requires the intended factories to conduct a comprehensive hydrogeological assessment. In the current study, the factories in Klang plan to abstract the groundwater for their plants. Therefore, the groundwater simulation is adopted to assess the negative impact from pumping activities. The conceptual model for the numerical simulation is developed based on the geological map, hydrogeological map, hydrological data, borehole logs, and static groundwater levels after well installations. The numerical model is successfully achieved with the root-mean-square error and correlation coefficient are less than 0.7 m and more than 0.9, respectively. The assessment results suggest the total pumping rate at the factories less than 7,200 m3/d to avoid the negative impact to surrounding wells. The calibrated model is essential to assist the authority to manage the groundwater resources in Klang.